Making it all normal: the role of the internet in problematic pregnancy. - Lowe, P; Powell, J; Griffiths, F; Thorogood, M; Locock, M (2009)
Women are actively encouraged to educate themselves about pregnancy from formal sources (e.g., information leaflets, antenatal classes, books). In addition, informal stories of pregnancy and birth are routinely told between women. However, increased prenatal testing means that more fetuses are diagnosed with abnormalities, shifting the information requirements during pregnancy. Traditional sources of information cannot cover all possible outcomes, and the Internet is beginning to fill this gap. In this article, we draw from interviews about experiences of antenatal screening and pregnancy to explore how the Internet provides a unique resource for problematic pregnancies. It allows access to information about rarer conditions beyond standard pregnancy texts, as well as personal narratives about conditions. Learning how others have coped or are coping in similar situations can help alleviate feelings of isolation, and also places women back in a familiar territory of shared pregnancy narratives.